RPA activates the XPF‐ERCC1 endonuclease to initiate processing of DNA interstrand crosslinks - Abdullah, U; McGouran, J; Brolih, S; Ptchelkine, D; El-Sagheer, A; Brown, T; McHugh, P (EMBO Press, 2017)
During replication‐coupled DNA interstrand crosslink (ICL) repair, the XPF‐ERCC1 endonuclease is required for the incisions that release, or “unhook”, ICLs, but the mechanism of ICL unhooking remains largely unknown. Incisions are triggered when the nascent leading strand of a replication fork strikes the ICL. Here, we report that while purified XPF‐ERCC1 incises simple ICL‐containing model replication fork structures, the presence of a nascent leading strand, modelling the effects of replication arrest, inhibits this activity. Strikingly, the addition of the single‐stranded DNA (ssDNA)‐binding replication protein A (RPA) selectively restores XPF‐ERCC1 endonuclease activity on this structure. The 5′–3′ exonuclease SNM1A can load from the XPF‐ERCC1‐RPA‐induced incisions and digest past the crosslink to quantitatively complete the unhooking reaction. We postulate that these collaborative activities of XPF‐ERCC1, RPA and SNM1A might explain how ICL unhooking is achieved in vivo.